P236 The role of histone arginine methylation in gene expression of airway smooth muscle cells in asthma. (15th November 2016) - Kaczmarek, KA; Clifford, RL; Patel, JK; Shaw, DE; Dowden, J; Knox, AJ
Abstract : Introduction and objectives: Asthma is estimated to affect at least 300 million people globally. About 25% of the patients do not respond to therapy; therefore we need to develop novel treatments. ASM cells have a crucial role in asthma, contributing to airway remodelling, inflammation and airflow obstruction. We have previously shown that epigenetic histone modifications, particularly histone lysine acetylation and methylation regulate the secretion of inflammatory mediators from ASM cells. Here we tested the hypothesis that histone arginine changes are also involved. Protein arginine N-methyltransferases (PRMTs) are the enzymes which catalyse histone arginine methylation (HRme, the addition of a methyl group to arginine residues on the N-terminal tails of histones), and inhibiting them represents a strategy to reduce the secretion of inflammatory mediators from ASM cells. Methods: Studies were performed in cultured human ASM cells from asthmatic and non-asthmatic donors at passage 6. PRMT expression in human ASM cells was investigated by qPCR. Protein levels of four PRMTs in human ASM cells were investigated by western blotting. As PMRT1 has previously been suggested to play a role in mouse asthma models, we studied the association of PRMT1 with eotaxin, IL-6, IP-10 and CXCL8 promoters in healthy ASM cells, under basal conditions and following stimulation with TNF-α (1ng/ml), by chromatin immunoprecipitation (ChIP). IgG was used as a negative control, while acetylated histone H4 (AcH4) was used as a positive control. Results: We found that ASM cells express the PRMT1, PRMT2, PRMT3, CARM1, PRMT5, PRMT6, PRMT7 and FBX011 mRNA and PRMT1, CARM1, PRMT5, and PRMT6 protein. The analysis showed no difference in the levels of expression between cells isolated from asthmatic and non-asthmatic donors. Under basal conditions, PRMT1 was associated with all of the promoters and association increased following 1 hour stimulation with TNF-α. Conclusions: ASM cells express a number of PRMTs at mRNA and protein levels. PRMT1 associates with a number of chemokine and cytokine promoters after TNF-α stimulation. PRMTs may have an important role in regulating chemokine production from ASM cells in asthma, and are a promising target for future investigations in asthma.